A study on consumer preference on social media reviews and online ads towards electronic gadgets with special reference to Chengalpattu. Issue 5 (4th July 2022) - Elayamurugan, S.; Umadevi, J.; Balakumar, V.
Abstract: Social media plays significant role in the modern era and it serves as reviews provider to the consumers by way of video reviews, blogs etc. The aim of this study is to understand consumer reviews on social media and online ads for electronic gadgets. For this purpose researcher has selected 110 respondents as sample size and it was surveyed through online questionnaire. Based on questionnaire, a hypothesis was framed. The data were analyzed and interpreted by applying various statistical tools. Findings of the study were that most of the consumers were aware of the new products by the way of social media and also through social media consumers are getting knowledge about the unique features, latest trends, comparison of other products, and usage of products.